EXCLUSIVE INTELLECTUAL PROPERTY HOLDER IN LEGAL PERSPECTIVE PROHIBITION OF MONOPOLY PRACTICES AND BUSINESS COMPETITION - Ida Nadirah; M Arkansyah (Proceeding International Seminar of Islamic Studies, 2022)
The holder of exclusive intellectual property rights is a legal subject who has special rights because the holder can make, use, sell, import, export, lease, deliver and distribute all of his work. This enormous power is very close to the nature of a prohibited monopoly in perspective Anti-monopoly Law and Business Competition. This study aims to explain the legal position of the exclusive right holder of intellectual property rights and to find out the anti-monopoly legal arrangements for the holders of exclusive intellectual property rights.This research is a normative juridicalresearch with descriptive analysis with a statutory approach that uses secondary data and is analyzedqualitatively. The position of exclusive intellectual property rights is clearly regulated in the Copyright Law, Patent Rights, Trademark Rights, Industrial Design Rights, Integrated Circuit Layout Design Rights and Trade Secrets.Law No. 5 of 1999 concerning the Prohibition of Monopolistic Practices and Business Competition that there are several monopolies that are allowed, namely in the form of actions or agreements aimed at implementing applicable laws and agreements. One of the laws is intellectual property law as regulated in Article 50 b of Law No. 5 of 1999 with the stipulation that the exclusive rights contained in the law do not cause unfair business competition and can harm the public interest.Keywords:Exclusive Rights, Intellectual Property, Prohibition of Monopolistic Practices and Business Competition